BIODIVERSITY ON THE PLATE: SUSTAINABLE DIETARY PATTERNS - Selvamohan T, Harishchander Anandaram, Vinayaka K.S, G. Jahirhussain, Parminder Singh Dehar, S. Monisha, (Chelonian Research Foundation, 2023)
Food and nutrition security, as well as a healthy lifestyle for current and future generations, are all facilitated by sustainable diets that have minimal negative effects on the environment. In addition to being culturally appropriate, accessible, equitable in terms of income, and economical, sustainable diets also maximize the use of both natural and human resources while protecting and honoring biodiversity and ecosystems. With regard to sustainable development, the idea of sustainable diets offers a chance to effectively forward the goals of ending poverty, achieving food and nutrition insecurity, and improving public health. Certain adjustments are necessary in order to achieve sustainable food practices. the availability of food in a sustainable manner that does not impede the achievement of other human rights, in quantities and qualities sufficient to satisfy nutritional requirements, free of contaminants, and acceptable within a certain culture. From food production at the farmer's stage to the consumer plate, several techniques of transformation are covered in this overview, along with the variables that affect the biodiversity of sustainable diets. Keywords: Sustainable diets, nutrition security, natural resources, biodiversity